Presence of Euglossa (Euglossa) amazonica outside of the Amazon Basin – biogeographic insights - Hinojosa-Diaz, Ismael A. (Journal of Melittology, 2013)
Distributional patterns of euglossine bees are often shadowed by the most noticeablefeatures of the group, their morphology and behavior. With the constant discovery of records ofeuglossine species in novel localities, and the ongoing systematic work in the group, especiallyin Euglossa Latreille, a better picture of the evolution and biogeography of these bees is beingdeveloped. Provided here is an account of new records of Euglossa (Euglossa) amazonica Dressleroutside of the Amazon Basin region are presented along with a brief discussion of distributionalpatterns of the genus in northwestern South America.